2020
DOI: 10.32602/jafas.2020.009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of firm characteristics and good corporate governance characteristics to earning management behaviors

Abstract: This research is carried out to investigate the influence of firm characteristics and good governance characteristics to earnings management behavior. Furthermore, the research is expanded to determine the predictive discretionary accruals models in Indonesia. The author utilizing firm listed in Indonesia Stock Exchange during 2014-2018 as research object. Design/methodology/approach: The research samples is selected by utilizing the purposive sampling method. In addition, the data analyze is conducted through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
2
9
0
2
Order By: Relevance
“…And found a significant negative impact of FS on the earning quality. This is consistent with the work of (Epps & Ismail, 2009;Hassan & Farouk, 2014;Jessica, 2020) and argued that the larger firms increases the value of discretionary accruals and do more earning manipulation because they want to present good financial condition of the firm in the market and wants to attract more investor so in doing so, they manipulate the earnings by making changes in the discretionary accruals and in return the earning quality is effected. While it is inconsistent with the work of some researchers who found a negative relationship between the firm size and earning management (Fodio et al, 2013).…”
Section: Results Of Fixed Effect Regression Modelsupporting
confidence: 88%
See 3 more Smart Citations
“…And found a significant negative impact of FS on the earning quality. This is consistent with the work of (Epps & Ismail, 2009;Hassan & Farouk, 2014;Jessica, 2020) and argued that the larger firms increases the value of discretionary accruals and do more earning manipulation because they want to present good financial condition of the firm in the market and wants to attract more investor so in doing so, they manipulate the earnings by making changes in the discretionary accruals and in return the earning quality is effected. While it is inconsistent with the work of some researchers who found a negative relationship between the firm size and earning management (Fodio et al, 2013).…”
Section: Results Of Fixed Effect Regression Modelsupporting
confidence: 88%
“…As (Waweru & Prot, 2018; González & García-Meca, 2014) found that the firm leverage positively related with the earnings management and indicated that the highly levered firms do more earning manipulation because they want to get the relaxation on the debt covenants and, in turn, decreases the earnings quality. While some studies like (Hassan & Farouk, 2014;Jessica, 2020) found a negative association between earning management and leverage. Hence they supported the view that the highly levered firm faces more scrutiny from the creditors, so they do less manipulation and, in turn, have higher earning quality.…”
Section: Leverage and Earnings Qualitymentioning
confidence: 96%
See 2 more Smart Citations
“…Ukuran auditor independen dalam perusahaan dapat dijadikan sebagai patokan kualitas audit perusahaan tersebut (Edi & Jessica, 2020). Oleh karena itu, berbagai peneliti yang berargumentasi dalam menentukan ukuran auditor berdasarkan kantor akuntan publik yang bekerja sama dengan BIG 4 atau 4 kantor akuntan publik terkenal (KPMG, EY, Deloitte & PwC).…”
Section: Ukuran Auditor Dan Manajemen Labaunclassified